Advances in the Ring Opening of Small-Ring Heterocycles with Organoboron Derivatives - Pineschi, Mauro (Synlett, 2014)
This is a personal account on how our research group has exploited trivalent boron-containing organic compounds to create new synthetic methods using small-ring heterocycles. A variety of new regioselective ring-opening reactions (including phenolysis and arylation) that exhibit unusual syn-stereoselectivities can be achieved by making use of the Lewis acidity of boron in aryloxyboranes. On the other hand, the use of the nucleophilic character of diboron derivatives permits regio- and stereocontrolled formation of new C–B bonds. An up-to-date critical coverage of recent relevant literature in the field is also provided.1 Introduction2 Ring-Opening Reactions with Triaryloxyboranes2.1 Carbon–Oxygen Bond Formation with Epoxides, Aziridines, Oxetanes, and Azetidines2.2 Carbon–Carbon Bond Formation: Stereoselective Arylations of Epoxides and Aziridines3 Ring Opening with Diboron Compounds3.1 Metal-Catalyzed and Metal-Free Borylations of Allylic Epoxides and Aziridines4 Conclusions
Keywords: ring opening; arylborates; arylation; epoxides; oxetanes; aziridines; azetidines; diboron derivatives